#TITLE_ALTERNATIVE# - MARILYN (NIM: 22710002); Tim Pembimbing: Prof. Ir. Lambok M. Hutasoit, M.Sc., Ph.D; Prof. Dr.I, NANCY
There are four factors that cause land subsidence in DKI Jakarta, namely: excessive groundwater extraction, building load, natural consolidation, and tectonic. In ten years (in 2001 Ã‚Â– 2011), GPS measurement in Rawa Buaya shows significant land subsidence, about 1.4 meters. Calculations with analytic and finite element method could be used, so we know contributes of land subsidence in Rawa Buaya. This study uses data from engineering geological bore log with 300 metres depth (full coring), data on subsidence from GPS measurement, and data on groundwater level from monitoring well. The result of this study (based on the calculation for ten years) are the following: contribution of natural consolidation is 0.918 m or 65.57%; groundwater extraction is 0.265 m or 18.92%; contribution of building load and tectonic is 0.217 m or 15.51% (the difference between subsidence from the measurement and from calculation of natural consolidation and groundwater extraction). The contribution of natural consolidation and groundwater extraction shows subsidence which vary with depth. The borrow material down to depth of two meters is thought to be still unconsolidated. It is also thought that hydro-compaction has occured because there is organic soil in 6 to 8 meters depth. This is also shown by void ratio and specific gravity which decrease with depth.